The enactment of public participation in rulemaking: a comparative analysis - De Francesco, Fabrizio; Tosun, Jale (Swiss political science review, 2023)
Abstract This study analyzes the enactment of public participation in rulemaking within the European Union and the Organization of Economic Cooperation and Development countries. It relies on an original dataset of administrative procedural acts and administrative laws concerning the making of delegated legislation. As 12 out of 39 countries enacted a procedure of notification, publication, and consultation between 1995 and 2015, the study focuses on courts while controlling for other domestic institutional determinants of legislative adoption and countries? interdependence. The empirical findings show that countries with a highly independent judiciary system are less likely to enact a comprehensive provision for public participation in rulemaking. This finding highlights a paradox, namely that political systems are more likely to adopt rulemaking to enhance democratic legitimacy if they are characterized by a judicial system that does not actively pursue the legality of rulemaking.